Structure–activity exploration of a small-molecule Lipid II inhibitor - Fletcher S; Yu W; Huang J; Kwasny SM; Chauhan J; Opperman TJ; MacKerell Jr AD; de Leeuw EPH (Dove Medical Press, 2015)
Steven Fletcher,1 Wenbo Yu,1,2 Jing Huang,1,2 Steven M Kwasny,3 Jay Chauhan,1 Timothy J Opperman,3 Alexander D MacKerell Jr,1,2 Erik PH de Leeuw4 1Department of Pharmaceutical Sciences, 2Computer-Aided Drug Design Center, University of Maryland, School of Pharmacy, Baltimore, MD, 3Microbiotix, Inc., Worcester, MA, 4Institute of Human Virology and Department of Biochemistry and Molecular Biology, University of Maryland, School of Medicine, Baltimore, MD, USA Abstract: We have recently identified low-molecular weight compounds that act as inhibitors of Lipid II, an essential precursor of bacterial cell wall biosynthesis. Lipid II comprises specialized lipid (bactoprenol) linked to a hydrophilic head group consisting of a peptidoglycan subunit (N-acetyl glucosamine [GlcNAc]–N-acetyl muramic acid [MurNAc] disaccharide coupled to a short pentapeptide moiety) via a pyrophosphate. One of our lead compounds, a diphenyl-trimethyl indolene pyrylium, termed BAS00127538, interacts with the MurNAc moiety and the isoprenyl tail of Lipid II. Here, we report on the structure–activity relationship of BAS00127538 derivatives obtained by in silico analyses and de novo chemical synthesis. Our results indicate that Lipid II binding and bacterial killing are related to three features: the diphenyl moiety, the indolene moiety, and the positive charge of the pyrylium. Replacement of the pyrylium moiety with an N-methyl pyridinium, which may have importance in stability of the molecule, did not alter Lipid II binding or antibacterial potency. Keywords: computer-aided drug design, Lipid II, antibiotics, phospholipid